UV-LED curing coating for new energy automobile coating as well as preparation method and application of UV-LED curing coating

By using modified epoxy acrylate resin and modified polydimethylsiloxane in UV-LED curing coatings, combined with a mixed photoinitiator with a specific ratio, the insufficient adhesion and machinery in the coating of new energy vehicles is solved. Poor performance, poor electrical insulation performance and brittleness after curing have been achieved, coatings with high adhesion, good mechanical properties and excellent electrical insulation performance have been improved, and the coating quality and efficiency have been improved.

CN119432183AActive Publication Date: 2025-02-14GUANGZHOU HANGUANG TECH CO LTD

Patent Information

Application Number
CN202411807409.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing UV-LED cured coatings have problems such as insufficient adhesion, poor mechanical properties, poor electrical insulation performance and brittleness after curing in new energy vehicle coatings, which limits its widespread adoption in high-end applications.

Method used

Modified epoxy acrylate resin and modified polydimethylsiloxane combined with a specific ratio of mixed photoinitiators, and improve the adhesion, mechanical properties and electrical insulation of the coating through the modified resin system and photoinitiator formulation. performance.

Benefits of technology

It significantly improves the adhesion and mechanical properties of the coating, enhances the electrical insulation performance, improves curing efficiency, reduces energy consumption, and improves the quality and efficiency of new energy vehicle coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179630490000111
    Figure BDA0005179630490000111
  • Figure BDA0005179630490000121
    Figure BDA0005179630490000121
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and particularly relates to a UV-LED curing coating for coating a new energy automobile as well as a preparation method and application of the UV-LED curing coating. The coating is prepared from the following components in parts by mass: 30 to 50 parts of modified epoxy acrylate resin, 10 to 20 parts of polyurethane acrylate resin, 10 to 20 parts of modified polydimethylsiloxane, 5 to 10 parts of a mixed photoinitiator, 1 to 3 parts of a photosensitizer, 1 to 3 parts of a flatting agent, 1 to 3 parts of an anti-aging agent, 1 to 3 parts of a de-foaming agent and 10 to 40 parts of water. The coating combines the advantages of a UV-LED light source, and adopts a specially designed resin system and photoinitiator formula, so that the adhesive force and mechanical property of the coating are improved, the curing efficiency of the coating is improved, meanwhile, the coating also has good electrical insulation property, and the quality and efficiency of automobile coating are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coatings, and specifically relates to a UV-LED curing coating for new energy vehicle coating, and a preparation method and application thereof. Background Art

[0002] In recent years, ultraviolet (UV) curing technology has been widely used in various fields due to its advantages such as high efficiency, rapidity, energy saving and low pollution, especially in the automotive coating industry, showing great potential. UV curing coatings can complete the curing process in a short time through ultraviolet irradiation of a specific wavelength, greatly shortening the production cycle, reducing energy consumption, and almost no VOCs emissions, making it an ideal environmentally friendly coating.

[0003] However, traditional UV-curing coatings have some limitations, such as insufficient adhesion to the substrate and poor weather resistance, which restrict their application in high-end automotive coatings. In addition, due to the limitations of UV light sources, traditional UV-curing coatings may not be fully cured in shadow areas during the curing process, affecting the coating quality.

[0004] With the development of LED technology, UV-LED, as a new light source, has higher energy efficiency, longer service life and better spectral controllability than traditional mercury lamps, which can effectively overcome the above problems. UV-LED curing coatings can not only achieve a more uniform and thorough curing effect, but also further reduce energy consumption and carbon footprint, which is in line with the development trend of the future automotive manufacturing industry.

[0005] However, existing UV-LED curing coatings still have some defects when used for new energy vehicle coating, which limit their widespread adoption in high-end applications. New energy vehicles use a variety of materials, such as metals, plastics, composite materials, etc., and existing UV-LED curing coatings have poor adhesion on certain substrates, especially on workpieces with complex shapes. Electrical components such as batteries and motors in new energy vehicles have high requirements for the electrical insulation performance of the coating, and existing UV-LED curing coatings cannot fully meet these requirements. In addition, some UV-LED curing coatings may become brittle and hard after curing, lack sufficient flexibility, and are prone to cracking when impacted or bent.

[0006] Therefore, there is an urgent need for a UV-LED curing coating suitable for new energy vehicle painting to solve the above problems. Summary of the invention

[0007] The purpose of the present invention is to provide a UV-LED curing coating suitable for new energy vehicle coating and its preparation method and application. The coating combines the advantages of UV-LED light source and adopts a specially designed resin system and photoinitiator formula, which not only improves the adhesion and mechanical properties of the coating, but also improves the curing efficiency of the coating. At the same time, it also has good electrical insulation properties, which significantly improves the quality and efficiency of automobile coating.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A UV-LED curing coating suitable for coating new energy vehicles comprises the following components in parts by mass: 30-50 parts of modified epoxy acrylate resin, 10-20 parts of polyurethane acrylate resin, 10-20 parts of modified polydimethylsiloxane, 5-10 parts of mixed photoinitiator, 1-3 parts of photosensitizer, 1-3 parts of leveling agent, 1-3 parts of antioxidant, 1-3 parts of defoaming agent and 10-40 parts of water.

[0010] Furthermore, the preparation method of the modified epoxy acrylate resin comprises the following steps:

[0011] (i) methyl acrylate (MMA), butyl acrylate (BA) and hydroxyethyl acrylate (HEA) are mixed, benzoyl peroxide (BPO) is added under stirring, the mixture is heated to 60-80° C., and stirring is continued for 2-4 hours to obtain an acrylate polymer;

[0012] (ii) mixing epoxy resin E51 with the acrylate polymer obtained in step (i), stirring, adding dibutyltin dilaurate (DBTDL), heating to 70-90° C., stirring for 1-2 hours, to obtain the modified epoxy acrylate resin.

[0013] Furthermore, in step (i), the mass ratio of methyl acrylate (MMA), butyl acrylate (BA) and hydroxyethyl acrylate (HEA) is 5:(2-4):(1-3), and the mass of benzoyl peroxide (BPO) is 1-1.5% of the total mass of methyl acrylate (MMA), butyl acrylate (BA) and hydroxyethyl acrylate (HEA).

[0014] Furthermore, in step (ii), the mass ratio of epoxy resin E51 to acrylate polymer is 1:(0.8-1.2), and the mass of dibutyltin dilaurate (DBTDL) is 0.2-0.6% of the epoxy resin E51.

[0015] Because epoxy acrylate resin has excellent adhesion, can be firmly attached to a variety of substrates, and it can be quickly cured under UV-LED light source, improve production efficiency, therefore, the present invention attempts to use epoxy acrylate resin as the matrix resin of curing coating, but the inventor found that unmodified epoxy acrylate resin is relatively brittle, and has insufficient flexibility. After curing, the coating is easy to crack when impacted or bent, therefore, the inventor has modified epoxy acrylate resin. Methyl acrylate, butyl acrylate and hydroxyethyl acrylate undergo free radical polymerization under the action of free radical initiator (BPO) to form acrylate polymer, and epoxy group is ring-opened under the action of catalyst (DBTDL) to form active intermediates, which can react with hydroxyl groups in acrylate polymer to form covalent bonds, further forming a cross-linked network. This modification measure further improves the adhesion and mechanical strength of the resin, and the introduction of butyl acrylate increases the flexible segment of the resin, making the resin difficult to crack or peel off when impacted or bent.

[0016] Furthermore, the preparation method of the modified polydimethylsiloxane comprises the following steps:

[0017] (a) γ-glycidyloxypropyltrimethoxysilane (KH560) and γ-aminopropyltrimethoxysilane (KH792) were added to polydimethylsiloxane in sequence, stirred for 10-15 minutes, dibutyltin dilaurate (DBTDL) was added, stirring was continued for 10-15 minutes, methyltrimethoxysilane (MTMS) was added, and stirring was continued for 10-15 minutes;

[0018] (b) heating the mixture obtained in step (a) to 70-90° C. and stirring the mixture for 2-5 hours to obtain the modified polydimethylsiloxane.

[0019] Furthermore, the mass ratio of the polydimethylsiloxane, γ-glycidyloxypropyltrimethoxysilane (KH560), γ-aminopropyltrimethoxysilane (KH792), and methyltrimethoxysilane (MTMS) is 10: (0.5-1.5): (0.5-1.5): (0.5-1.5), and the mass of the dibutyltin dilaurate (DBTDL) is 0.3-1% of the mass of the polydimethylsiloxane.

[0020] Adding polydimethylsiloxane to the formula of the present invention can improve the electrical insulation of the coating, but the addition of unmodified polydimethylsiloxane will affect the overall adhesion of the coating, which can easily cause the coating to fall off or peel off. The inventors found that the adhesion of polydimethylsiloxane can be significantly improved while maintaining excellent electrical insulation after modification using the method of the present invention. The amino group in KH792 can react with the epoxy group in KH560 to form a cross-linked structure, and the amino group further reacts with the silanol group in the polydimethylsiloxane to form a covalent bond, thereby enhancing the adhesion and mechanical properties of the resin. The trimethoxysilane group in MTMS undergoes a hydrolysis reaction to generate a silanol group, which undergoes a condensation reaction with the silanol group in the polydimethylsiloxane, further enhancing the cross-linked network, so that the modified polydimethylsiloxane has excellent adhesion and mechanical properties.

[0021] Furthermore, the mixed photoinitiator is a mixture of 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1-hydroxycyclohexyl phenyl ketone (184), and 2-isopropylthioxanthone (ITX), and the mass ratio of the three is (3-5): (1-2): (1-2).

[0022] The present invention uses three photoinitiators in a specific ratio, which can improve the spectral response range, improve the curing depth and speed, and improve the coating performance. 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) mainly absorbs long-wave ultraviolet light, 1-hydroxycyclohexyl phenyl ketone (184) mainly absorbs medium-wave ultraviolet light, and 2-isopropylthioxanthone (ITX) mainly absorbs short-wave ultraviolet light. Through compounding, it can be ensured that there is an efficient photoinitiating effect in different wavelength ranges, and the overall curing efficiency is improved. The compounded photoinitiators can act synergistically to ensure that the polymerization reaction can be effectively initiated from the surface layer to the deep layer, thereby achieving uniform curing. In addition, the compounded photoinitiator can accelerate the generation and transfer of free radicals, increase the curing speed, and shorten the production cycle. The compounded photoinitiator can reduce the occurrence of side reactions and improve the comprehensive performance of the coating, wherein the synergistic effect of TPO and 184 can reduce the yellowing phenomenon, and the addition of ITX can improve the weather resistance and chemical resistance of the coating. In addition, the compound photoinitiator can optimize the cross-linking density of the coating and improve the hardness, wear resistance and adhesion of the coating.

[0023] Furthermore, the photosensitizer is 2-hydroxy-2-methyl-1-phenylpropanone or 2,2-dimethoxy-2-phenylacetophenone.

[0024] Furthermore, the leveling agent is an acrylate leveling agent.

[0025] Furthermore, the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(nonylphenyl)phosphite, and 2,2,6,6-tetramethylpiperidinol.

[0026] Furthermore, the defoaming agent is fatty acid ester or polyacrylate.

[0027] The present invention also provides a method for preparing the above-mentioned UV-LED curing coating, comprising the following steps:

[0028] (1) mixing modified epoxy acrylate resin, polyurethane acrylate resin and modified polydimethylsiloxane and stirring for 10-20 minutes;

[0029] (2) Add the mixed photoinitiator and photosensitizer and continue stirring for 10-20 minutes until evenly dispersed;

[0030] (3) Add leveling agent, antioxidant and defoamer, continue stirring for 10-20 minutes, and evenly disperse;

[0031] (4) Add water to adjust the viscosity and stir for 10-20 minutes to obtain the UV-LED curing coating.

[0032] The present invention also provides application of the above-mentioned UV-LED curing coating in the painting of new energy vehicles.

[0033] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0034] The UV-LED curing coating provided by the present invention significantly improves the adhesion and mechanical properties of the coating by using modified epoxy acrylate resin as the base resin, and reduces the risk of the coating falling off or peeling off; the addition of modified polydimethylsiloxane significantly improves the electrical insulation of the coating, so that it exhibits good insulation effect under high voltage and high frequency environment; the compound photoinitiator improves the photoinitiating effect, improves the curing efficiency, and can use a lower power light source, further saving energy and cost, thereby significantly improving the quality and efficiency of new energy vehicle coating. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise specified, the raw materials in the examples are all common commercially available products, and the following is an exemplary description:

[0037] Epoxy resin E51 was purchased from Nan Ya Plastics Industrial Co., Ltd.;

[0038] Polydimethylsiloxane was purchased from Dow Corning (China) Co., Ltd., DC200;

[0039] Polyurethane acrylate resin was purchased from Covestro (Shanghai) Co., Ltd., Bayhydro l UH 2245;

[0040] Epoxy acrylate resin was purchased from Eastman Chemical, EBECRYL 8200;

[0041] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide (TPO) was purchased from BASF (China) Co., Ltd.;

[0042] 1-Hydroxycyclohexylphenylketone (184) was purchased from Eastman Chemical (China) Co., Ltd.;

[0043] 2-Isopropylthioxanthone (I TX) was purchased from LANXESS Chemical (China) Co., Ltd.;

[0044] 2-Hydroxy-2-methyl-1-phenylpropanone was purchased from Clariant (China) Co., Ltd.;

[0045] Polyacrylate copolymer was purchased from BYK Chemical (China) Co., Ltd., BYK-354;

[0046] Butyl stearate was purchased from Nanjing Chemical Reagent Co., Ltd.

[0047] Polytetrafluoroethylene emulsion was purchased from Shanghai San Ai Fu New Materials Co., Ltd., F-101.

[0048] Example 1

[0049] This embodiment provides a method for preparing a modified epoxy acrylate resin, comprising the following steps:

[0050] (i) Methyl acrylate (MMA), butyl acrylate (BA) and hydroxyethyl acrylate (HEA) are mixed in a clean reaction bottle, the reaction bottle is placed on a magnetic stirrer, the stirrer is started, and benzoyl peroxide (BPO) is slowly added under stirring, and stirring is continued for 5 minutes. The reaction bottle is moved to a constant temperature water bath, the temperature is set to 70° C., and heating and stirring are continued for 3 hours to complete a free radical polymerization reaction. After the reaction is completed, the reaction bottle is taken out of the water bath and naturally cooled to room temperature to obtain an acrylate polymer;

[0051] The mass ratio of methyl acrylate (MMA), butyl acrylate (BA) and hydroxyethyl acrylate (HEA) is 5:3:2, and the amount of benzoyl peroxide (BPO) added is 1% of the total mass of the monomers (the total mass of MMA, BA and HEA);

[0052] (ii) weighing epoxy resin E51 and putting it into a clean reaction bottle, placing the reaction bottle on a magnetic stirrer, starting the stirrer, stirring at a speed of 600 rpm, adding the acrylate polymer obtained in step (i) under stirring, and continuing to stir for 10 minutes, adding dibutyltin dilaurate (DBTDL), and continuing to stir for 10 minutes, moving the reaction bottle to a constant temperature water bath, setting the temperature to 80° C., heating and continuing to stir for 1.5 hours to complete the reaction between the epoxy group and the hydroxyl group, and after the reaction is completed, taking the reaction bottle out of the water bath and naturally cooling it to room temperature to obtain a modified epoxy acrylate resin;

[0053] The mass ratio of epoxy resin E51 to acrylate polymer is 1:1, and the added mass of dibutyltin dilaurate (DBTDL) is 0.5% of the epoxy resin E51.

[0054] Example 2

[0055] This embodiment provides a method for preparing modified polydimethylsiloxane, comprising the following steps:

[0056] (1) Add polydimethylsiloxane to a clean reaction bottle, place the reaction bottle on a magnetic stirrer, start the stirrer, stir at 600 rpm, add KH560 and KH792, continue stirring for 10 minutes, add dibutyltin dilaurate (DBTDL), continue stirring for 10 minutes, add MTMS, and continue stirring for 10 minutes;

[0057] The mass ratio of polydimethylsiloxane, KH560, KH792 and MTMS is 10:1:1:1, and the mass of dibutyltin dilaurate (DBTDL) is 0.5% of the mass of polydimethylsiloxane;

[0058] (2) The reaction bottle was moved to a constant temperature water bath, the temperature was set to 80° C., and the mixture was heated and stirred continuously for 3 hours. After the reaction was completed, the reaction bottle was taken out of the water bath and naturally cooled to room temperature to obtain modified polydimethylsiloxane.

[0059] Example 3

[0060] The present embodiment provides a UV-LED curing coating suitable for new energy vehicle coating, which includes the following components by mass: 40 parts of modified epoxy acrylate resin, 12 parts of polyurethane acrylate resin, 15 parts of modified polydimethylsiloxane, 8 parts of mixed photoinitiator, 2 parts of photosensitizer (2-hydroxy-2-methyl-1-phenylpropanone), 2 parts of leveling agent (polyacrylate copolymer), 1 part of antioxidant (2,6-di-tert-butyl-p-cresol), 1 part of defoaming agent (butyl stearate), and 20 parts of water.

[0061] The modified epoxy acrylate resin was prepared according to the method of Example 1.

[0062] The modified polydimethylsiloxane was prepared according to the method of Example 2.

[0063] The mixed photoinitiator is a mixture of 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1-hydroxycyclohexyl phenyl ketone (184), and 2-isopropylthioxanthone (I TX), and the mass ratio of the three is 4:1:1.5.

[0064] The preparation method of the above-mentioned UV-LED curing coating comprises the following steps:

[0065] (1) mixing modified epoxy acrylate resin, polyurethane acrylate resin and modified polydimethylsiloxane and stirring for 15 minutes;

[0066] (2) Add the mixed photoinitiator and photosensitizer and continue stirring for 15 minutes to ensure uniform dispersion;

[0067] (3) Add leveling agent, antioxidant and defoamer, and continue stirring for 15 minutes to ensure uniform dispersion;

[0068] (4) adding water to adjust the viscosity of the coating, and stirring for 15 minutes to obtain the UV-LED curing coating.

[0069] Example 4

[0070] The present embodiment provides a UV-LED curing coating suitable for coating new energy vehicles, which includes the following components by mass: 35 parts of modified epoxy acrylate resin, 20 parts of polyurethane acrylate resin, 12 parts of modified polydimethylsiloxane, 6 parts of mixed photoinitiator, 2 parts of photosensitizer (2-hydroxy-2-methyl-1-phenylpropanone), 2 parts of leveling agent (polyacrylate copolymer), 1 part of antioxidant (2,6-di-tert-butyl-p-cresol), 1 part of defoaming agent (butyl stearate), and 20 parts of water; the rest is the same as Example 3.

[0071] Comparative Example 1

[0072] This comparative example provides a UV-LED curing coating suitable for coating new energy vehicles, which differs from Example 3 in that the modified epoxy acrylate resin is replaced by an unmodified epoxy acrylate resin.

[0073] Comparative Example 2

[0074] This comparative example provides a UV-LED curing coating suitable for coating new energy vehicles, which is different from Example 3 in that butyl acrylate is not added during the preparation of the modified epoxy acrylate resin.

[0075] Comparative Example 3

[0076] This comparative example provides a UV-LED curing coating suitable for coating new energy vehicles, which differs from Example 3 in that the modified polydimethylsiloxane is replaced by unmodified polydimethylsiloxane.

[0077] Comparative Example 4

[0078] This comparative example provides a UV-LED curing coating suitable for coating new energy vehicles, which differs from Example 3 in that KH792 is not added during the preparation of the modified polydimethylsiloxane.

[0079] Comparative Example 5

[0080] This comparative example provides a UV-LED curing coating suitable for new energy vehicle coating, which is different from Example 3 in that the mixed photoinitiator is 2,4,6-trimethylbenzoyldiphenylphosphine oxide and methyl benzoylformate, with a mass ratio of 2:1.

[0081] Comparative Example 6

[0082] This comparative example provides a UV-LED curing coating suitable for new energy vehicle coating, which is different from Example 3 in that the mass ratio of TPO, 184, and I TX in the mixed photoinitiator is 1:1:1.

[0083] Comparative Example 7

[0084] This comparative example provides a UV-LED curing coating suitable for new energy vehicle coating, which differs from Example 3 in that the modified polydimethylsiloxane is replaced by polytetrafluoroethylene emulsion.

[0085] Comparative Example 8

[0086] This comparative example provides a UV-LED curing coating suitable for new energy vehicle coating, which is different from Example 3 in that it includes the following components, measured by mass: 55 parts of modified epoxy acrylate resin, 5 parts of polyurethane acrylate resin, 7 parts of modified polydimethylsiloxane, 8 parts of mixed photoinitiator, 2 parts of photosensitizer (2-hydroxy-2-methyl-1-phenylpropanone), 2 parts of leveling agent (polyacrylate copolymer), 1 part of antioxidant (2,6-di-tert-butyl-p-cresol), 1 part of defoaming agent (butyl stearate), and 20 parts of water.

[0087] Performance Testing

[0088] The cured coatings prepared in Example 3 and Comparative Examples 1-8 were coated on a substrate, and after being cured using a UV-LED light source, the performance was tested.

[0089] The hardness is tested according to GB / T 6739-2006 "Pencil Determination of Coating Hardness"; the adhesion is tested according to GB / T 9286-1998 "Scratch Test for Paint and Varnish Films"; the flexibility is tested according to GB / T 1731-1993 "Determination of Flexibility of Paint Films"; the impact strength is tested according to GB / T1732-1993 "Test Method for Impact Resistance of Paint Films"; the wear resistance is tested according to GB / T1768-2006 "Determination of Abrasion Resistance of Paints and Varnishes (Rotating Rubber Wheel)"; the complete drying time of the coating is tested according to GB T37362.1-2019 "Drying Test for Paints and Varnishes Part 1: Determination of Complete Dry State and Complete Drying Time"; the electrical insulation is tested according to GB / T1410-2006 "Determination of Volume Resistivity and Surface Resistivity of Solid Insulating Materials".

[0090] The test results are shown in Table 1.

[0091] Table 1 Performance test results

[0092]

[0093]

[0094] According to the above results, it can be seen that the UV-LED curing coating prepared by the present invention has excellent adhesion, mechanical strength, curing performance and electrical insulation performance. In Comparative Example 1, the modified epoxy acrylate resin is replaced with an unmodified epoxy acrylate resin. The unmodified epoxy acrylate resin lacks a flexible segment and has a strong intermolecular force, which leads to an increase in the brittleness of the coating and a decrease in hardness. The unmodified epoxy acrylate resin has fewer functional groups and a weak chemical bond with the substrate, so the adhesion decreases. In Comparative Example 2, butyl acrylate is not added during the preparation of the modified epoxy acrylate resin. Also due to the lack of a flexible segment, the intermolecular force is strong, which leads to an increase in the brittleness of the coating and a decrease in hardness. In Comparative Example 3, the modified polydimethylsiloxane is replaced with an unmodified polydimethylsiloxane. The unmodified polydimethylsiloxane is mainly physically mixed in the resin system and lacks effective chemical bonding, resulting in a decrease in adhesion and other properties. In Comparative Example 4, the modified polydimethylsiloxane was prepared without adding KH792, and the cross-linked structure formed by the prepared polydimethylsiloxane was weak, so the mechanical properties were reduced. In Comparative Examples 5 and 6, the types or ratios of the mixed photoinitiators were changed, and the complementary advantages of various photoinitiators could not be brought into play, resulting in reduced curing efficiency and reduced mechanical properties. In Comparative Example 7, the modified polydimethylsiloxane was replaced with polytetrafluoroethylene emulsion. Although polytetrafluoroethylene emulsion has excellent electrical insulation properties, after being added to the coating system, it may affect the distribution and interaction of other components, resulting in a decrease in the overall electrical insulation performance. In addition, the molecular chain of polytetrafluoroethylene emulsion is relatively rigid and lacks sufficient flexible segments, which causes the coating to crack easily when bent or impacted. In Comparative Example 8, the ratio of the components was changed, especially the ratio of modified epoxy acrylate resin was increased, while the ratio of polyurethane acrylate resin and modified polydimethylsiloxane was reduced, resulting in a decrease in the overall performance of the coating. Although the modified epoxy acrylate resin has good adhesion, excessive use will increase the brittleness of the coating and reduce its flexibility and adhesion.

[0095] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A UV-LED curing coating suitable for new energy vehicle coating, comprising the following components by mass: 30-50 parts of modified epoxy acrylate resin, 10-20 parts of polyurethane acrylate resin, 10-20 parts of modified polydimethylsiloxane, 5-10 parts of mixed photoinitiator, 1-3 parts of photosensitizer, 1-3 parts of leveling agent, 1-3 parts of antioxidant, 1-3 parts of defoaming agent, and 10-40 parts of water.

2. The UV-LED curing coating according to claim 1, characterized in that: The preparation method of the modified epoxy acrylate resin comprises the following steps: (i) mixing methyl acrylate, butyl acrylate and hydroxyethyl acrylate, adding benzoyl peroxide under stirring, heating to 60-80° C., and continuing stirring for 2-4 hours to obtain an acrylate polymer; (ii) mixing epoxy resin E51 with the acrylate polymer obtained in step (i), stirring, adding dibutyltin dilaurate, heating to 70-90° C., stirring for 1-2 hours, to obtain the modified epoxy acrylate resin.

3. The UV-LED curing coating according to claim 2, characterized in that: In step (i), the mass ratio of methyl acrylate, butyl acrylate and hydroxyethyl acrylate is 5:(2-4):(1-3), and the mass of benzoyl peroxide is 1-1.5% of the total mass of methyl acrylate, butyl acrylate and hydroxyethyl acrylate.

4. The UV-LED curing coating according to claim 2, characterized in that: In step (ii), the mass ratio of epoxy resin E51 to acrylate polymer is 1:(0.8-1.2), and the mass of dibutyltin dilaurate is 0.2-0.6% of the epoxy resin E51.

5. The UV-LED curing coating according to claim 1, characterized in that ,,The preparation method of the modified polydimethylsiloxane comprises the following steps: (a) adding γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltrimethoxysilane to polydimethylsiloxane in sequence, stirring for 10-15 minutes, adding dibutyltin dilaurate, continuing stirring for 10-15 minutes, adding methyltrimethoxysilane, and continuing stirring for 10-15 minutes; (b) heating the mixture obtained in step (a) to 70-90° C. and stirring the mixture for reaction for 2-5 hours to obtain the modified polydimethylsiloxane.

6. The UV-LED curing coating according to claim 5, characterized in that: The mass ratio of the polydimethylsiloxane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane and methyltrimethoxysilane is 10:(0.5-1.5):(0.5-1.5):(0.5-1.5), and the mass of the dibutyltin dilaurate is 0.3-1% of the mass of the polydimethylsiloxane.

7. The UV-LED curing coating according to claim 1, characterized in that: The mixed photoinitiator is a mixture of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone and 2-isopropylthioxanthone, and the mass ratio of the three is (3-5): (1-2): (1-2).

8. The UV-LED curing coating according to claim 1, characterized in that: The photosensitizer is 2-hydroxy-2-methyl-1-phenylpropanone or 2,2-dimethoxy-2-phenylacetophenone, the leveling agent is an acrylate leveling agent, the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(nonylphenyl)phosphite, 2,2,6,6-tetramethylpiperidinol, and the defoamer is fatty acid ester or polyacrylate.

9. A method for preparing the UV-LED curing coating according to any one of claims 1 to 8, comprising the following steps: (1) mixing modified epoxy acrylate resin, polyurethane acrylate resin and modified polydimethylsiloxane and stirring for 10-20 minutes; (2) Add the mixed photoinitiator and photosensitizer and continue stirring for 10-20 minutes until evenly dispersed; (3) Add leveling agent, antioxidant and defoamer, continue stirring for 10-20 minutes, and evenly disperse; (4) Add water to adjust the viscosity and stir for 10-20 minutes to obtain the UV-LED curing coating.

10. Application of the UV-LED curing coating according to any one of claims 1 to 8 in the painting of new energy vehicles.

Citation Information

Patent Citations

  • LED-UV-cured transfer printing adhesive and preparation method thereof

    CN105733389A

  • Environment-friendly water-based flexographic printing UV ink

    CN109135412A

  • Single-component dealcoholized transparent silicone sealant, preparation method and application thereof

    CN109280533A

  • UV-LED light-curing vacuum coating primer and preparation method thereof

    CN110437731A

  • UV curable metallic decorative compositions

    US20150344722A1

Cited By

  • UV skin-touch coating for nursing materials as well as preparation method and application of UV skin-touch coating

    CN120082284A

  • Water-based UV curing coating and production process thereof

    CN121652675A

  • Aqueous uv-curing coating and process for its production

    CN121652675B